PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN GRAND ROCKY HOTEL - Gusti, Via; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study is aimed tof the determine the effect of Interpersonal Communication towards Employee Productivity Grand Rocky Hotel Bukittinggi. The research type is using associative causal correlation approach. The population of this study were permanent employees of the Grand Rocky Hotel Bukittinggi with amounted of114people. Selection of the sample using proportionate stratified random sampling technique (54). Collecting data using a questionnaire based on Likert Scale which has been tested for validity and reliability. The results showed that in general, the interpersonal communication was classified as good category and the labor productivity was classified as passbly. Based on regression analysis the study had found influence siginifikansi between interpersonal communication with labo rproductivity by 23%. Keywords: Communication, Interpersonal, Productivity, Work